2014
DOI: 10.1155/2014/769239
|View full text |Cite
|
Sign up to set email alerts
|

CD80 and CD86 Costimulatory Molecules Differentially Regulate OT-II CD4+T Lymphocyte Proliferation and Cytokine Response in Cocultures with Antigen-Presenting Cells Derived from Pregnant and Pseudopregnant Mice

Abstract: Immune phenomena during the preimplantation period of pregnancy are poorly understood. The aim of our study was to assess the capacity for antigen presentation of splenic antigen-presenting cells (APCs) derived from pregnant and pseudopregnant mice in in vitro conditions. Therefore, sorted CD11c+ dendritic cells and macrophages F4/80+ and CD11b+ presenting ovalbumin (OVA) were cocultured with CD4+ T cells derived from OT-II mice's (C57BL6/J-Tg(TcraTcrb)1100Mjb/J) spleen. After 132 hours of cell culture, prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Moreover, previous studies demonstrated the upregulated expression of CD80 and CD86 on murine splenic antigen presenting cells such as dendritic cells and macrophages at the pre-implantation period (day 3.5 pc). This was shown to be crucial in modulating T regulatory cell (Treg) abundance, cytokine production, and ultimately pregnancy outcome (33,34). A follow up study examining splenic B cells showed similar results, with CD86 protein expression significantly increased in normal pregnant mice compared to abortion-prone models at pre-implantation (35).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, previous studies demonstrated the upregulated expression of CD80 and CD86 on murine splenic antigen presenting cells such as dendritic cells and macrophages at the pre-implantation period (day 3.5 pc). This was shown to be crucial in modulating T regulatory cell (Treg) abundance, cytokine production, and ultimately pregnancy outcome (33,34). A follow up study examining splenic B cells showed similar results, with CD86 protein expression significantly increased in normal pregnant mice compared to abortion-prone models at pre-implantation (35).…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, the retention of differentiation markers CD24 and CD21 as well as expression of activation marker CD38 suggested that uterine B cells are mature, but yet to have differentiated into antibody-producing plasma cells (41,42). Furthermore, ∼20 and 50% of IL-10 negative uterine B cells express the ligands CD80 and CD86, respectively ( Figure 5B) which suggests that a significant proportion of the uterine B cells have the capacity for co-stimulating T cell activation, potentially leading to negative regulation by way of Treg expansion and modification of cytokine production (33,34). Interestingly, the small proportion observed as IL-10 + B cells within the uterine B cell population exhibited higher expression of co-stimulatory molecules CD80 and CD86 as well as CD27, an activation marker of memory and plasmablast lineages in murine B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of CD86 but not CD80 on APCs is observed in other diseases as well such as systemic lupus erythematosus [ 44 ]. In contrast to CD80, CD86 expression on APCs drives the differentiation of T cell towards a Th2 profile [ 12 , 13 , 14 , 15 , 16 ]. Previous studies showed that in chronic HBV-infected livers, most T cells are Th0-like cells and contribute to the production of Th2-type cytokines by producing IL-4 and IL-5 in addition to a low level of IFN-γ production [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CD80 and CD86 might have different roles in regulating the T helper (Th) responses. While CD80 expression on APCs mainly drives T cell differentiation towards a Th1 profile, CD86 leads the differentiation towards a Th2 profile [ 12 , 13 , 14 , 15 , 16 ]. Interestingly, during HBV infection T cell response, especially in liver infiltrating lymphocytes, is associated with the production of IL-10 and Th2 cytokines rather than Th1 cytokines, and Th1 responses are weak in chronic HBV-infected patients when compared with resolver [ 2 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD80 mainly drives T-cell diferentiation towards a Th1 proile and CD86 leads the diferentiation towards a Th2 proile [38][39][40][41][42]. T-cell response in HBV infection mainly initiates Th2 immune response rather than Th1.…”
Section: Monocytes/macrophages In Hbv Infectionmentioning
confidence: 99%